PENGARUH INDEPENDENSI DAN KOMITMEN ORGANISASI TERHADAP KUALITAS AUDIT - Riswan -; Lydia Sumiyati (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2013)
This research aims to obtain the empirical evidences whether independence andorganizational commitment partially give the positive influences to audit’s quality. The research isconducted to the independent auditor from various Public Accountant Offices by spreading closedquestioners to the chosen location as the sample. The technique sample taking used sampling area,then the data were analysed using Structural Equation Modelling that based on covariance structure,called Linear Structural Relations (LISREL). This modeling technique consists of the measurementmodel and structural model. Measurement model used to measure the dimensions that form a factoror latent variable, whereas the structural model describes the influence and relations betweenconstructs or latent variables.The research’s result concludes that independence and organization commitment partiallygive the positive influences and significant to audit’s quality.